'A new experience and a new concept': a study on postgraduate students' experiences of parent–infant observation. Issue 3 (2nd September 2018) - Matharu, Gurleen Kaur; Perez, Alejandra
ABSTRACT: Parent–infant observations often bring about difficult emotional reactions for the observer. These difficulties form part of the learning experience and are often explored in the observer's personal analysis and, to some extent, in the observation seminars. However, many postgraduate students are not in personal analysis and are carrying out observations for the first time. There has been little research exploring their experiences of conducting these observations and this study aims to better understand their thoughts and feelings. Six former students of postgraduate courses at the Anna Freud National Centre for Children and Families run in conjunction with University College London were interviewed (four female and two male). A qualitative Interpretative Phenomenological Analysis of the interviews revealed how the observation was experienced as a complex journey they felt was difficult to bear emotionally but, despite their struggles, they all indicated a great appreciation of this learning experience.